Fuel consumption evaluation of SI engine using start-stop technology - Abas, M.A.; Wan Salim, W.S.; Ismail, M.I.; Rajoo, S.; Martinez-Botas, R. (Universiti Malaysia Pahang, 2017)
The engine start-stop technology is gaining acceptance as a key technology adopted by manufacturers to improve the fuel economy of passenger cars. This technology shuts the engine off when a vehicle is at a stop. The inherent issue with the implementation of the start-stop technology in hot climates is the requirement for the air-conditioning system to be in constant operation which reduces the duration of engine shut-off during vehicle stops, and consequently, nullifying the benefit of the system. The aim of this study is to evaluate the potential fuel consumption improvements on a spark ignition engine when using the start-stop technology in real conditions of the Malaysian tropical climate, with consideration towards cabin comfort temperature. The result provides useful insight and enables vehicle manufacturers to assess whether such technology is feasible for implementation in tropical climates. A 1.6 litre spark ignition engine was modelled along with an air-conditioning system model using a commercial one-dimensional engine simulation gas dynamic software. A vehicle driving profile of engine speed and engine torque obtained from real driving on Malaysian roads was captured and used as the boundary conditions for the simulation. Iterations of the start-stop strategy were simulated to further explore the possible impacts on fuel consumption. The result of this study showed that the duration of engine shut-off during vehicle stops becomes shorter due to the necessity of the air-conditioning system to operate in maintaining the cabin’s comfort temperature. With the shorter duration of engine shut-off, the fuel consumption improvement stemming from the start-stop technology is reduced from the average of 20.7 % to 11.0 %, therefore, addressing the concerns on the application of the start-stop technology in hot climate countries and the opportunity to further optimise fuel consumption.